Inovasi Pembelajaran Berbasis Animasi 2 Dimensi Untuk Mahasiswa Berkebutuhan Khusus (Studi Kasus Mahasiswa Tuli di Usahid Surakarta) - Anwar, Ahmad Khoirul (Kawruh: Journal of Language Education, Literature and Local Culture, 2023)
Universitas Sahid Surakarta has accepted students with special needs since 2012 and has been running for the last ten years. Managing students with special needs is challenging because it requires a special effort. Most students with disabilities are deaf. The fact faced during the last ten years is that students with special needs, especially deaf, do not all understand sign language. Not all of them also understand the language of lip movements. They can only communicate using written language. However, their ability to understand sentences is also minimal in the sense of only being able to understand short sentences. Students with special needs have difficulty understanding or digesting long and many sentences. Those conditions affect the process of receiving teaching materials. From the problems faced, solutions are needed for learning innovations for students with special needs. The innovation is to make learning media based on 2-dimensional animation. The production of this learning media was monitored and evaluated by the Directorate of Learning and Student Affairs (Belmawa) of the Directorate General of Higher Education, Research and Technology (Ditjen Diktiristek) last September 2022. The learning media that have been made have also undergone a process of testing, improving, and improving, which takes more than two semesters.